2017
DOI: 10.1038/s41598-017-14539-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MST1 as a potential early detection biomarker for colorectal cancer through a proteomic approach

Abstract: Colorectal cancer (CRC) is a common malignant neoplasm worldwide. It is important to identify new biomarkers for the early detection of CRC. In this study, magnetic beads and the Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) platform were used to analyse CRC and healthy control (HC) serum samples. The CRC diagnosis pattern was established to have a specificity of 94.7% and sensitivity of 92.3% in a blind test. The candidate biomarker serine/threonine kinase 4 (STK4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 48 publications
1
30
0
1
Order By: Relevance
“…A previous study concluded that MST1 and cyclophilin D expressions were notably reduced in gemcitabine-resistant pancreatic cancer tissues and cell lines (24). MST1 was also found to be elevated in control patients compared with patients with stage I colorectal cancer during early colorectal cancer examinations (26). MST1 could also be activated by gemcitabine, making it capable of facilitating cancer cell death by means of complexation with mitochondrial protein cyclophilin D (24).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study concluded that MST1 and cyclophilin D expressions were notably reduced in gemcitabine-resistant pancreatic cancer tissues and cell lines (24). MST1 was also found to be elevated in control patients compared with patients with stage I colorectal cancer during early colorectal cancer examinations (26). MST1 could also be activated by gemcitabine, making it capable of facilitating cancer cell death by means of complexation with mitochondrial protein cyclophilin D (24).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those already reported in the literature for other cancers, such as breast cancer, 29 hepatocellular carcinoma, 30 and colorectal cancer. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Mst1 is a downstream factor of the Hippo pathway, which has been implicated in several pathological processes, including diabetic cardiomyopathy, osteoblast differentiation ( 45 ) and milk fat metabolism disorder ( 46 ). Furthermore, Mst1 downregulation has been identified as a potential early detection biomarker for numerous types of cancer, including colorectal cancer ( 47 ), breast cancer ( 48 ), pancreatic cancer ( 49 ), lung cancer ( 50 ) and liver cancer. At the molecular level, Mst1 has been reported to be associated with the ER stress response ( 51 ), cellular oxidative stress ( 52 ), epithelial-to-mesenchymal transition ( 53 ), transforming growth factor β-mediated tissue fibrosis ( 54 ) and mitophagy ( 7 ).…”
Section: Discussionmentioning
confidence: 99%